To solve this sysetm of equations, line the equations up

3x+6y=6

2x-3y=4

Multiple each term in the second equation by 2, so it is

4x-6y=8

Now line them up again.

3x+6y=6

4x-6y=8

Add, so the sum is

7x=14

x=2

Substitute the x=2 into one of the original equations.

3x+6y=6

3*2+6y=6

6+6y=6

6y=0

y=0

The solution is (2,0)

3x+6y=6

2x-3y=4

Multiple each term in the second equation by 2, so it is

4x-6y=8

Now line them up again.

3x+6y=6

4x-6y=8

Add, so the sum is

7x=14

x=2

Substitute the x=2 into one of the original equations.

3x+6y=6

3*2+6y=6

6+6y=6

6y=0

y=0

The solution is (2,0)